G112(P) Foetal Neurology: A study of referral pattern and outcomes in a tertiary centre. (27th April 2016) - Ginbey, E; Tallur, K Kamath; Kandasamy, J; Gallo, P; Kaliaperumal, C; Cowan, S; Cooper, S; Boardman, J
Abstract : Introduction: Screening for foetal abnormality is an important part of antenatal care. When a neurological abnormality is detected in the foetus the woman is referred to the Paediatric Neurosciences team for counselling. 1 This study investigates the pattern of abnormalities found and their outcome. Methods: Patients were identified from the Paediatric Neurosciences departmental database, which contained referrals from 2005–2015. Further information on the patients and their outcomes was collected from their electronic notes. Results: Of the 68 patients identified in the database, 66 pregnancy outcomes were documented. Ultrasonography (US) was used in all patients, and US combined with Magnetic Resonance Imaging (MRI) were the most used investigation methods. Figure 1 illustrates the gestational age that abnormalities were first detected by US. Myelomeningocele was the most frequent abnormality detected (n = 30) (Figure 2 ). The pregnancy was terminated in 39% (n = 26) cases (Figure 3 ). The pattern of decision to terminate was different for the various abnormalities: 75% of open lipped schizencephalies were terminated, in comparison to 0% of Dandy Walker malformations. 32 children were alive at recent follow up of which 31 had the correct diagnosis prenatally; 18 of which had had additions to their diagnosis. Conclusions: There is little literature on the patterns of antenatal referrals to the Paediatric Neurosciences teams and their subsequent outcomes. This study describes the pattern of abnormalities detected, their frequency and ultimate outcomes. This study can be used to assist the Paediatric Neurologists and Neurosurgeons when counselling women who have been found to have neurological abnormalities on antenatal screening. Reference: Scher, Mark S. "Topical Review: Fetal and Neonatal Neurologic Case Histories: Assessment of Brain Disorders in the Context of Fetal-Maternal-Placental Disease. Part 1: Fetal Neurologic Consultations in the Context of Antepartum Events and Prenatal Brain Development." Journal of child neurology 2003;18 (2):85–92